Interest in The Theme of Expression Faced with The Appreciation of Class 6 SD 4 PLADEN - Khalimatus Sa'diyah, Isnaini; Wijayanto, Wasis; Fajrie, Nur (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
This study aims to find out the influence of the interest in drawing themes of expression on the ability of appreciation in 6th grade students in SD 4 Plates. This analysis uses a combination of quantitative and qualitative research methods/mixed methods. This research uses a saturated sampling technique with the subject of the research, which is a student of 6th grade SD 4 Pladen which is 19. The free variable (X) is an interest drawing the theme of the expression (independent) while the bound variables (Y) are the appreciation of the student (dependent). Our data-gathering techniques use lifts, interviews, observations, and documentation. In this study, we used quantitative descriptive data analysis techniques and used simple linear regression tests. Further, the data analyzed using qualitative descriptive analysis to strengthen the results of quantitative research. The results of the study showed that there was an influence of the interest variable drawing expression (X) on the appreciation ability variable (Y) of 22.8%.